Weather conditions and weather forecast on the planets of the solar system based on the behavior of Rossby waves - Gavrilov Milivoj B.; Lazić Lazar; Đorđević Jasmina (Glasnik Srpskog Geografskog Društva, 2010)
Out of all atmospheric processes on the planets of the Solar System, special attention will be devoted here to leading circulation of planetary or global scales, known as Rossby waves. These waves occur in all rotating fluids that have relative movement to the rotation system. Rossby waves exert dominant influence on so-called global weather. Based on the knowledge of some properties of Rossby waves are made approximate analysis of weather conditions on the planets of the Solar System. Also, these considerations can serve as an introduction to weather forecasting on the planet. .